Portraits of Thai Politics - "Ray, Jayanta Kumar" ([?])
This book offers the political memoirs of three representative figures in modern Thai politics. Two of them, Nai Thawee Bunyaketu and Mom Rajawongse Seni Pramoj, are eminent civilian politicians. Both have occupied some of the highest administrative-political offices, including that of the Prime Minister. Both have fought hard against the predominance of military politicians in Thai politics, and suffered much in the struggle for the establishment of genuine parliamentary democracy in Thailand. This book also presents the political memoirs of Lady La-iad Pibul Songgram, the widow of Field Marshal Pibul Songgram. She was a direct participant in and a first-hand observer of many critical events of Thai politics during 1932-57. All these memoirs are expected to constitute significant primary sources for research on politics in Thailand.
Keywords: Politics and Government